Port- city renewal in developing countries. The waterfront at Dar Es Salaam, Tanzania - Hoyle, Brian (ERDKUNDE, 2002)
The global spread of urban waterfront redevelopment, hitherto largely confined to advanced countries, is now starting to impact upon developing countries too as they seek to revive historic cities in contexts including postcolonialism, multiculturalism, heritage conservation, tourism development, inter-port competition and globalization. This paper reports on the experience of Dar es Salaam, Tanzania where waterfront redevelopment is making progress as an element in urban conservation, with the support of local, national and international organizations. Within a theoretical context and regional frameworks, the paper includes an account of the condition of the Dar es Salaam urban waterfront as observed from the landward and maritime sides in the later 1990s. The case study is related to wider problems and policy issues, to relevant literature and to experience elsewhere.